2022
DOI: 10.1002/er.7914
|View full text |Cite
|
Sign up to set email alerts
|

Construction of effective transmission channels by anchoring metal‐organic framework on side‐chain sulfonated poly(arylene ether ketone sulfone) for fuel cells

Abstract: A series of novel organic-inorganic hybrid membranes assembled by side-chain type sulfonated poly(arylene ether ketone sulfone) with amino groups (Am-SPAEKS-DBS) and ZIF-67 were prepared. Am-SPAEKS-DBS containing double bonds was synthesized by condensation polymerization, and the AMPS was grafted onto the main chain by post sulfonation. ZIF-67 was prepared by an ordinary solvent method. The structures of ZIF-67, Am-SPAEKS-DBS, and hybrid membranes were analyzed by proton nuclear magnetic resonance ( 1 H NMR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…18 For instance, Liu et al studied a sulfonated N-heterocyclic containing poly(aryl ether ketone)s with suspended phenyl moities for PEMFCs, which showed a swelling rate of 5.6%, and proton conductivity of 9.8-103 mS cm À1 at 75 C. 19 Ju et al constructed an effective proton transport channel by introducing metal-organic framework on the linked of sulfonated poly(arylene ether ketone sulfone). The MOFpolymer membrane showed a proton conductivities of 0.054-0.069 S cm À1 at 30 C, 0.088-0.116 S cm À1 at 80 C. 20 Traizole pendant sulfonated poly(arylene ether ketone sulfone) was reported to have a proton conductivity of 0.166 S cm À1 at 120 C, which was more significant than that of Nafion 117. 21 Itoh et al synthesized a phosphoric acid doped hyperbranched polymer for PEMFC and obtained a proton conductivity of 1.2 Â 10 À5 and 2.6 Â 10 À6 S cm À1 due to the hyperbranched structure providing better water permeability.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…18 For instance, Liu et al studied a sulfonated N-heterocyclic containing poly(aryl ether ketone)s with suspended phenyl moities for PEMFCs, which showed a swelling rate of 5.6%, and proton conductivity of 9.8-103 mS cm À1 at 75 C. 19 Ju et al constructed an effective proton transport channel by introducing metal-organic framework on the linked of sulfonated poly(arylene ether ketone sulfone). The MOFpolymer membrane showed a proton conductivities of 0.054-0.069 S cm À1 at 30 C, 0.088-0.116 S cm À1 at 80 C. 20 Traizole pendant sulfonated poly(arylene ether ketone sulfone) was reported to have a proton conductivity of 0.166 S cm À1 at 120 C, which was more significant than that of Nafion 117. 21 Itoh et al synthesized a phosphoric acid doped hyperbranched polymer for PEMFC and obtained a proton conductivity of 1.2 Â 10 À5 and 2.6 Â 10 À6 S cm À1 due to the hyperbranched structure providing better water permeability.…”
Section: Introductionmentioning
confidence: 94%
“…Ju et al constructed an effective proton transport channel by introducing metal–organic framework on the linked of sulfonated poly(arylene ether ketone sulfone). The MOF‐polymer membrane showed a proton conductivities of 0.054–0.069 S cm −1 at 30°C, 0.088–0.116 S cm −1 at 80°C 20 . Traizole pendant sulfonated poly(arylene ether ketone sulfone) was reported to have a proton conductivity of 0.166 S cm −1 at 120°C, which was more significant than that of Nafion 117 21 .…”
Section: Introductionmentioning
confidence: 94%
“…Numerous polymers have been explored as the AEMs' backbones, including poly(arylene ether ketone) (PEK), 9,10 poly(arylene ether sulfone) (PES), 11,12 poly(phenylene oxide) (PPO), 13,14 polybenzimidazole (PBI), 15,16 poly(crown ether) (PCE) 17,18 and several heteroatom-free polymers like poly(arylene alkylene), [19][20][21] polyfluorenes 22 and polyalkenes. 23 In addition, various functional cationic groups, such as quaternary ammonium, 10,20-22 imidazolium, 9,11 guanidinium, 24 phosphonium, 25 pyrrolidinium, 26 piperidinium 27,28 and some metal-based cations, 29 have been studied and utilized for AEMs. In particular, recent research demonstrated the cationic groups carrying alkyl chains or bulky groups showed better alkaline stability, which could be attributed to the steric hindrance effect.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial PEMs of Nafion membranes produced by DuPont exhibit good stability and high proton conductivity 8,9 . However, the disadvantages, such as excessively expensive price, high fuel permeability, strong dependence on water, and rapid performance degradation at elevated temperatures, limit the large‐scale use of Nafion membranes 10,11 . Sulfonated aromatic polymers with excellent mechanical properties and chemical stability are considered to be possible to replace Nafion membranes 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…dependence on water, and rapid performance degradation at elevated temperatures, limit the large-scale use of Nafion membranes. 10,11 Sulfonated aromatic polymers with excellent mechanical properties and chemical stability are considered to be possible to replace Nafion membranes. 12,13 Wang et al prepared sulfonated poly(ether ether ketone) (SPEEK) membranes with different sulfonation degrees, and the proton conductivities of SPEEK membranes with degrees of sulfonation (DS) of 39% and 47% were close to that of Nafion115 membranes.…”
mentioning
confidence: 99%